Role of Prebiotic, Probiotic and Symbiotic Diets on Bacterial proliferation in Feed and Intestine of African (Clarias gariepinus) Catfish - A. Abdul-Malik; M. Aliyu-Paiko; K. M. Adamu; A. Aliyu-A; J. N. Mohammed (Journal of Applied Sciences and Environmental Management, 2023)
The influence of prebiotic, probiotic and symbiotic diet on microbial proliferation was studied using an in vitro method. In the present trial, formulated diets were supplemented with prebiotic (Sargassum muticum), probiotic (Parkia biglobosa) and combination of Parkia biglobosa and Sargassum muticum (symbiotic diet). Bacteria proliferation in supplemented feeds, small and large intestine of the African catfish, Clarias gariepinus fed the formulated diets were evaluated. The feeding trial that lasted 12 weeks was conducted in plastic aquaria, with each treatment replicated three times. A control diet containing only the feed ingredients was also formulated and fed for the same period. The result showed bacteria proliferation was lowest in the control diet and highest in feed supplemented with prebiotic. Low bacteria proliferation was observed in the small intestine of fish fed symbiotic diet while highest proliferation was recorded in the fish fed prebiotic diet. The result also revealed the lowest bacteria proliferation in the large intestine of fish fed symbiotic diet and highest in fish fed probiotic diet. Using the cell morphology and biochemical characteristics of bacteria isolates in supplemented feed, Clarias gariepinus small and large intestine, the result indicated the presence of some Lactic Acid Bacteria (LAB) known to produce a variety of antimicrobial substances which are able to stop the development of foodborne diseases by inhibiting the growth of food spoilage and pathogenic organisms.